PERLINDUNGAN TERHADAP KONSUMEN PENGGUNAAN BAN BEKAS DAUR ULANG MENURUT UNDANG UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Ewa Kukuh juwanda; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This research is motivated by the widespread business activities of recycling used tires which are now one of the businesses that are mostly occupied by Small and Medium Industries (IKM). From the economic side, this type of business is expected to be able to make a significant contribution to the national economy. However, in terms of legal protection for consumers of recycled tire products, until now the legal rules used to guarantee the rights of consumers who use recycled tires against all possibilities are Law Number 8 of 1999 concerning Consumer Protection.The type of research used in writing this law is a sociological legal research, with a descriptive nature of research. The focus of the research in this thesis is: 1. Analyzing legal protection for consumers who use recycled used tires according to Law Number 8 of 1999 concerning Consumer Protection 2. Analyzing the responsibilities of recycled used tire business actors according to Law Number 8 of 1999 concerning Consumer protection?The results of this study indicate that: (1) Legal protection in the form of legal rules for consumers who use recycled tires Simamora and Ardath Ban Pekanbaru in the pre-transaction stage and the transaction has not been implemented by business actors in accordance with Law Number 8 of 1999 concerning Consumer Protection. where business actors have not provided clear information to consumers regarding the condition of marketed recycled tires and also business actors have sold used goods that should not be traded. (2) in carrying out their responsibilities, the Simamora and Ardath Tire Recycling Business Actors are already responsible for their business activities in accordance with Law Number 8 of 1999 concerning Consumer Protection. Where business actors in good faith have provided compensation for damage to recycled tires used by consumers.Keywords: Consumer, Recycling, Used Tires, Protection